Dedi Mulyadi Political Branding in Identifying Sundanese Purwakarta Characters - Nila Nurlimah; Aziz Taufik Hirzi; Leti Kamila; Nur Fitriastuti (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
This study examines how the politics of branding conducted by the Regent of Purwakarta Dedi Mulyadi in organizing and actualizing Purwakarta as a city with Sundanese characters. This study uses a qualitative method with a case study approach, intending to map various political branding efforts undertaken by Dedi Mulyadi, both from policies in different sectors and implementation in the field. The qualitative data analysis steps such as data reduction, data presentation, and conclusion carried out simultaneously.The results of this research are Dedi Mulyadi has taken political branding strategies and has been carrying out Sundanese nuanced political activities consistently and intensively, both through policy and direct socialization to citizens practically in an interactive, consistent, active, and participatory manner. Sundanese culture in the vision and mission of the local government implemented in local government policies in various sectors; education, tourism, and spatial sector. Dedi Mulyadi internalized Sundanese culture through innovative and creative ideas by following the changing times. Dedi Mulyadi's has brought Purwakarta as a city of culture as